ChemInform Abstract: Organic Stereochemistry. Part 1. Symmetry Elements and Operations, Classification of Stereoisomers. Issue 19 (18th April 2013) - Testa, Bernard; Vistoli, Giulio; Pedretti, Alessandro
Abstract Review: 56 refs.